Risk Assessment for International Construction Projects - UĞURAL, MEHMET NURETTİN (Niyazi Özdemir, 2023)
International projects are inherently exposed to unforeseeable and complex risk scenarios. This study aimed to assess and identify the critical risk factors in international contracting projects, based on the analytic hierarchy process (AHP) method. The most compelling risks that are faced by the construction firms in the Afghanistan market are determined primarily by meta-analysis. According to the data obtained from this analysis, the priorities of the risks and the degree of severity between each other are determined by using the AHP method. This research enhances the current body of knowledge about the possible encountered threats for investing the high-risk construction markets. The findings of the study may also help contractors to develop strategies "to bid or no-bid decisions" for high-risk markets.
Uluslararası İnşaat Projeleri için Risk Değerlendirmesi
Keywords: International Construction; Project Management; Risk Assessment; AHP